PENGENDALIAN FOOD COST OLEH COST CONTROLLER PADA PAPILLON ECHO BEACH CANGGU - I Made Kerta Wijaya; Ni Luh Putu Sri Widhiastuty (Universitas Triatma Mulya, 2021)
This study focuses on controlling the cost of food materials in the hotel industry. This study aims to determine the efforts, constraints and solutions in controlling food costs at Papillon Echo Beach, and to identify the causes of the difference between actual cost and standard cost. The data collection techniques in this study used observation, interviews, and documentation techniques and were processed using two data analysis techniques, namely qualitative descriptive analysis and quantitative descriptive analysis. This study gives an indication that: 1) efforts to control food cost at Papillon Echo Beach have been implemented but have not been optimal, this is indicated by some differences between the actual cost and the standard cost in 2020; 2) there are several obstacles in the effort to control food cost, namely the uncertainty of room occupancy, instability of food material price, there is no general store, competition, miscommunication, and menu variations; 3) efforts that can be made to overcome obstacles, namely holding promotions, signing contracts with suppliers, performing storage techniques, maintaining stable prices, and evaluating employee performance; 4) an increase in food costs occurred in April 2020 by 67.79%, exceeding the standard food cost of 35% caused by the COVID-19 pandemic, obstacles to the distribution of foodstuffs from outside of Bali, stockpiling from the previous month, the demage of storage equipment, and lack of promotional effort.